Aerodynamic study of vehicle mounted cargo boxes: A comparative study between roof boxes and tow bar mounted cargo boxes using CFD - Sandberg, Marcus (My University, 2022)
Ever rising CO2 emission needs to be mitigated and there are many ways forward. For the car industry the way forward spells ever increasing energy efficiency and the introduction of electric vehicles. When extra cargo capacity is required for a passenger vehicle, it is common to install a roof box, for example if one is ought to go skiing. However energy efficiency, electric vehicles and roof boxes does not go hand in hand and compared to vehicle producers, and it is rare to optimise the box with a thorough aerodynamic study due to its investment cost. Initial literature surveys indicate that a substantial power increase is required, as stated Cd values are in the range of 30% increased compared to the car alone. Furthermore the frontal area is increased, increasing the power requirements even further. The IXTAbox is a recent innovation to combat the shortfall of the roof box through putting the box on the tow bar, rather than the roof. As it lies in the wake of the vehicle it is expected that the required power increase is significantly lower compared to a roof box as no added area is done, and Cd should have a minimal impact as it lies in the wake. But it is not possible to answer how much the drag increase, and what areas of the IXTAbox is sensitive to change, which is why this thesis is conducted. To answer the questions at hand, Computational Fluid Dynamics (CFD) shall be used. With CFD, this thesis has studied and presented CdA values for two roof box models, furthermore six IXTAboxes has been studied, and finally aerodynamic improvements to the IXTAbox has been shown. From the study, it has been seen that a roof box can increase CdA by almost 40% while the IXTAbox increase the CdA by 4-11% depending on its size. Finally, the important flow features when implementing the IXTAbox include that the base pressure on the trunk of the car increases compared to when only simulating the car. On the other hand, an additional stagnation point occur as the IXTAbox captures the flow coming from the underbody, essentially removing the function of the car’s diffusor. With that in mind, the most successful design improvements on the IXTAbox + car achieved a lower CdA value than the car on its own, making it a very interesting innovation to study further as it mitigates the shortfall of the roof box, heavily increased power requirements.
Keywords: Aerodynamics; vehicles; cargoboxes; roofboxes; CFD; drag; dragreduction; pressurerecovery; fluid mechanics